Pengaruh Jarak Tanam terhadap Produksi Tiga Sayuran Indigenous - Faiqotul Himma; Bambang Sapta Purwoko (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2013)
ABSTRACTThe purpose this research was to determine the effects of plant spacing (population) on growth and yield of three indigenous vegetables (kemangi, kenikir, and katuk). The research was conducted at Cikabayan experimental farm in Darmaga, Bogor from April until November 2010. The experiment design was a Randomized Complete Block Design one factor with four treatments of plant spacing or population: 25 cm × 13. 33 cm (population 300 000 plants ha- 1), 25 cm × 16 cm (population 250 000 plants ha-1), 25 cm × 20 cm (population 200 000 plants ha- 1), and 25 cm × 26.67 cm (population 150 000 plants ha- 1), with three replications. Observations included plant height, number of leaves, number of branches, weight yields per plant and weight yield per plot. The experiment showed that plant spacing of kemangi did not influence vegetative growth, weight yields per plant and weight yield per plot. Plant spacing of kenikir influenced number of leaves, number of branches, weigth yields per plant. Plant spacing of katuk did not influence vegetative growth, weight yields per plant and weight yield per plot.Key words: katuk, kemangi, kenikir, population, vegetative growth, yieldABSTRAKPenelitian ini bertujuan untuk melihat pengaruh jarak tanam dalam populasi terhadap pertumbuhan dan hasil dari tiga sayuran indigenous (kemangi, kenikir, dan katuk). Penelitian dilaksanakan di Kebun Percobaan Cikabayan, Darmaga Bogor dari April hingga November 2010. Penelitian menggunakan Rancangan Kelompok Lengkap Teracak satu faktor dengan empat perlakuan jarak tanam: 25 cm × 13:33 cm (populasi 300 000 tanamanha-1), 25 cm × 16 cm (populasi 250 000 tanaman ha-1), 25 cm × 20 cm (populasi 200 000 tanaman ha-1), dan 25 cm × 26.67 cm (population 150 000 tanaman ha-1), dengan tiga ulangan. Pengamatan meliputi tinggi tanaman, jum lah daun, jumlah cabang, bobot hasil per plot. Jarak tanam kenikir berpengaruh terhadap jumlah daun, jumlah cabang, hasil per tanaman . Jarak tanam tidak berpengaruh terhadap pertumbuhan vegetatif , hasil per tanaman dan hasil per plot kemangi dan katuk.Kata kunci: katuk, kemangi, kenikir, populasi, pertumbuhan vegetatif, hasi